Формування розвивального освітнього середовища в початковій школі України у 70-х роках ХХ ст. - Смолюк, Світлана Володимирівна; Smoliuk, Svitlana V. (Львівський національний університет імені Івана Франка, 2016)
У статті обгрунтовано особливості формування розвивального освітнього середовища в початковій школі України у 70-х роках ХХ ст. Автором досліджено, що в окреслений період державою декларувались прогресивні стратегії щодо підвищення якості освіти, реалізації її виховувальної функції у педагогічному процесі, однак вирішення поставлених завдань здійснювалося на тлі ідейно-комуністичної спрямованості, формування фізично здорової та дисциплінованої (слухняної) людини для розбудови суспільства, продуктивної праці в економічному та сільськогосподарському секторі господарства країни. Значно менше уваги приділялось індивідуалізації навчання й виховання, розвитку творчості учнів та ініціативи. Виявлено, що в 1970-х роках освітня політика в країні спрямовувалась на створення відповідного предметно-просторового середовища в початковій школі. Акцентовано на інтенсивному забезпеченні шкіл технічними засобами навчання, облаштуванні шкільних кінотеатрів для реалізації, відповідності естетики інтер’єру критеріям ідейно-політичної спрямованості.

The article substantiates the formation of developing the educational environment in elementary school Ukraine in the 70-es years of XX century. The author investigated that outlined during period the state declared a progressive strategies for improving the quality of education, implementation of its educational function in the study process, but the task was carried out against the background of ideological communistic orientation, forming physically healthy and disciplined (obedient) person for the development of society, productive work at the economical and agricultural sectors of the country. Much less attention was paid to the individualization of training and educational process, student’s creativity and initiative. Revealed that in 1970 the country's educational policy was aimed at introducing a subject-spatial environment in elementary school, which was heavily used system of a desk study. The attention to schools providing intensive technical facilities, equipping of school cinemas for implementation, compliance of interior aesthetics to the criteria of ideological and political orientation. Determined that in elementary education, special attention was paid to the activation of the adaptive function of the environment of the school. Accent in the training and education of the growing personality carried out primarily on preparing them for active and hard work for the benefit of society, trouble-free performance of professional functions in future activities. Developing of the idea of forming educational environment after school and extracurricular work with younger students is valuable. The focus of efforts of the government on creating conditions for the full development of personality problems caused strengthening educational work with children in the classroom and outside of elementary school art creates a positive learning environment.
Formation of developing educational environment in elementary school of Ukraine at the 70-es years of XX century
Keywords: розвивальне освітнє середовище; початкова школа України; предметно-просторе середовище школи; естетичне середовище; developmental learning environment; primary school of Ukraine; object-space school environment; aesthetic environment